Application of a novel orthodontic medical record in cleft lip and palate patients - Leiva, Noemi (2019)
The medical record is a medico-legal document that allows the registration of a patient and his/her health problem. During the last 33 years, a unique model of orthodontic medical record has been used specifically for orthodontic care in patients with cleft palate at the Craniofacial Malformation Unit of the University of Chile. The objective of this work is to present an orthodontic medical record that can be used for both, clinical and teaching purposes.